Reconciling Theory and Context: How Geographic Frictions Sever the FDI-Growth Link in Maluku, Indonesia - Arsad Matdoan; Teddy Christianto Leasiwal; Korneles Sangur (Pattimura Proceeding, 2026)
This study analyzes the influence of Foreign Direct Investment (FDI), Exports, and Employment on Economic Growth in Maluku Province, Indonesia, an archipelagic region characterized by significant geographic frictions. Employing time-series data (2000-2024) and the ARDL cointegration approach, we find that exports and employment opportunities significantly drive economic growth. However, contrary to conventional growth theory, FDI exhibits a statistically insignificant direct effect. We argue that this anomaly is not merely a statistical artifact but is empirically attributable to the mediating role of geographic frictions—exorbitant logistics costs and crippling infrastructure deficits inherent to the archipelago context. This finding challenges the direct applicability of standard FDI-growth models in archipelagic economies and underscores the critical importance of transaction costs and economic geography as intervening variables. The policy implication is that development strategy must prioritize reducing geographic frictions through logistics infrastructure and target export-oriented, labor-intensive investments rather than pursuing FDI quantity indiscriminately.